Predicting interest and achievement in learning exponential and logarithmic functions - Rovan, Daria; Pavlin-Bernardić, Nina; Vlahović-Štetić, Vesna (2014)
The aim of this study was to analyze the role of prior knowledge, mathematics self-efficacy and value, triggered and maintained situational interest and perceived competence in the prediction of emerging individual interest and achievement in learning exponential and logarithmic functions. The participants were 186 third-grade high school students from five general-program gymnasiums in Croatia. The study was conducted in four waves during two months while students learned exponential and logarithmic functions in school. During that period, we tested students’ initial and final knowledge in that area and they filled out questionnaires on their self-efficacy and task value in mathematics, triggered situational interest, perceived competence in performing exponential and logarithmic functions, maintained situational interest and emerging individual interest. Interest measures had two components – emotional experience and task value. The results showed that the achievement in the final exam at Time 4 was positively predicted by initial test, Time 3 maintained interest and Time 3 perceived competence. Both components of emerging individual interest in Time 4, as well as perceived competence, were positively predicted by Time 1 task value. Emotional experience component of individual interest was also predicted by Time 2 and Time 3 interest-emotional experience, while task value component of individual interest was predicted by Time 3 interest-task value and perceived competence was predicted by Time 3 self-efficacy. This study provides support for the model of interest development (Hidi & Renninger, 2006) and shows that maintained interest has a very important role in in learning and motivation development.
ENG